Optimality of type I orthogonal arrays for cross-over models with correlated errors - Joachim Kunert; R. J. Martin (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1998)
We show that binary designs for cross-over models obtained from orthogonal arrays are universally optimal under correlated errors.
Keywords: 519; Carry-over effect; Change-over design; Cross-over design; Dependent observations; Generalized least-squares; Optimal design; Orthogonal arrays; Repeated measurements design